Evaluation of Quality of Life in Women with Abortion Experience in Tehran 2015 - 2016 - Feizollahi, Narjes; Nahidi, Fatemeh; Sereshti, Manije; Nasiri, Maliheh; Azadpour Motlagh, Asieh (Advances in Nursing & Midwifery, 2020)
Introduction: Abortion as a traumatic event in life can have consequences on women’s Individual-social quality of life. This study aimed to determine the quality of life of women with an abortion experience. Methods: In this descriptive cross-sectional study in 2016, Convenience sampling was applied to select 165 women with a history of abortion from health centers affiliated to Shahid Beheshti University. A demographic, fertility, and the World Health Organization Quality of Life Questionnaire were used to collect data. Descriptive statistics (mean, standard deviation) and Pearson’s correlation tests were administered to analyze the data by SPSS 20. Results: The mean score of quality of life in research units was 78,43, mean score of quality of life dimensions, physical restraint 75.23, emotional limit 77.40, vitality 70,90 , emotional health 49.38, Social score 72.03, pain 73.08 and health was 79.61, the mean score of each dimension was above average, respectively. There was a Significant relationship between age (p = 0.003), women’s education (p = 0.001), family income (p = 0.001), number of abortion/previous absences (p = 0.002), gestational age at the time of abortion (p = 0.005), visualization of the fetus in sonography (p = 0.000), pregnancy request (p = 0.003), history of infertility (p = 0.001), abortion method (p = 0.002) and fetus heart hearing (p = 0.005) with quality of life. Conclusions: Given the impact of abortion on women’s quality of life and the importance of family and community health, reproductive health policy should be aimed at reducing the consequences of abortion and improving the quality of life.